Beadlore of the Uma' Jalan Kenyah - Colfer, C.J.P.; Pelibut, Juk Along (2001)
This is a brief article, built on the knowledge of “Pui Pelibut” with whom Colfer stayed when she lived in Long Segar, East Kalimantan in 1979-80 (and from time to time since then). The article examines the beads in two necklaces, identifying their probable ultimate sources in Europe or China, and providing the Kenyah name for the particular bead. The Kenyah have an elaborate knowledge system (which is currently dying) pertaining to their beads, including gender, economic value, names, and connections with the soul.